Решите уравнение:(2х+3)^2-3(2х+3)(7х-5)+2(7х-5)^2=0

0 голосов
35 просмотров

Решите уравнение:
(2х+3)^2-3(2х+3)(7х-5)+2(7х-5)^2=0


Алгебра (12 баллов) | 35 просмотров
0

там первое выражение в квадрате?

0

да)

Дано ответов: 2
0 голосов

4x+6x+9-3+14x^2-10x+21x-15+2+49x-70x+25=0 (вычёркиваем подобные и которые приводят к нулю)
9-3+14x^2-15+2+25=0 (складываем числа)
получается 18+14x^2=0

(34 баллов)
0 голосов

(2х+3)^2-3(14x-10x+21x-15)+2(7x-5)=0
(2x+3)^2-43x+45+2(7x-5)=0
4x^2+12x+81-42x+3-63x+45+2(7x-5)=0
4x^2-93x+126+2(7x-5)=0
4x^2-93x+126+14x-10=0
4x^2-79x+116=0
D=6241-4*4*116=6241-1856=4385

(59 баллов)